Pengembangan LKPD Berbasis PBL Materi SPLDV untuk Memfasilitasi KPMM Peserta Didik Kelas VIII SMP/MTs: Penelitian - Indriya Sandi; Sakur; Titi Solfitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop a Student Worksheet (LKPD) based on Project Based Learning (PBL) for the topic of Systems of Linear Equations in Two Variables (SPLDV) that facilitates the Mathematical Problem-Solving Ability (KPMM) of eighth-grade junior high school (SMP/MTs) students. The developed product is expected to meet the criteria of validity and practicality. The subjects of this study were six eighth-grade students from SMP Negeri 2 Sabak Auh during the even semester. This research employed the Research and Development (R&D) method, with data collection carried out using a practicality questionnaire. The product trial was conducted on a small scale involving six students. The validation results from two expert lecturers and one practitioner showed a validity level of 96.34%. Meanwhile, the practicality level—assessed based on aspects of appearance, language, learning material, problem-solving ability, and ease of use—reached 86.68%. It can thus be concluded that the PBL-based LKPD on the SPLDV topic developed in this study meets the criteria of being valid and practical for use in learning activities aimed at enhancing students’ Mathematical Problem-Solving Ability.